The Rise and Fall, and the Rise (Again) of Feminist Research in Music: 'What Goes Around Comes Around'. Issue 2 (3rd July 2017) - Macarthur, Sally; Bennett, Dawn; Goh, Talisha; Hennekam, Sophie; Hope, Cat
Abstract : This article reports from a two-phase study that involved an analysis of the extant literature followed by a three-part survey answered by seventy-one women composers. Through these theoretical and empirical data, the authors explore the relationship between gender and music's symbolic and cultural capital. Bourdieu's theory of the habitus is employed to understand the gendered experiences of the female composers who participated in the survey. The article suggests that these female composers have different investments in gender but that, overall, they reinforce the male habitus given that the female habitus occupies a subordinate position in relation to that of the male. The findings of the study also suggest a connection between contemporary feminism and the attitudes towards gender held by the participants. The article concludes that female composers classify themselves, and others, according to gendered norms and that these perpetuate the social order in music in which the male norm dominates.